Una aproximación a la escultura y a la pintura en la iglesia de San Nicolás de Bari y en el convento del Santo Sepulcro de Zaragoza en los siglos del Barroco: An approach to sculpture and painting in the church of San Nicolás de Bari and in the convent of the Holy Sepulchre in Zaragoza in the Baroque centuries - Martín Marco, Jorge (Artigrama, 2025)
ResumenLa iglesia de San Nicolás de Bari y el convento de canonesas del Santo Sepulcro de Zaragoza conservan una gran cantidad de bienes muebles de los siglos XVII y XVIII. Aunque algunos de ellos han recibido la atención de los estudiosos, otros se custodian en almacenes y su conocimiento resulta escaso. Con este panorama general se quiere dar a conocer determinadas piezas para que se investigue sobre ellas y puedan restaurarse, protegerse y difundirse correctamente.AbstractThe church of San Nicolás de Bari and the Convent of Canonesses of the Holy Sepulchre in Zaragoza contain a large number of movable assets from the 17th and 18th centuries. Although some of them have received the attention of scholars, others are kept in warehouses and little is known about them. This general overview aims to raise awareness of certain pieces so that they can be researched and properly restored, protected and disseminated.KeywordsZaragoza, Saint Nicholas of Bari, Holy Sepulchre, Baroque, Sculpture, Painting.